THE ACQUISITION OF COMMUNICATIVE COMPETENCE AS ONE IMPORTANT ASPECT OF CULTURE: HOW SHOULD COMMUNICATIVE COMPETENCE BE BUILT? - Willem Saragih (BAHAS, 2016)
As the arts and the manifestations of human intellectual achievement regarded collectively, culture, which is realized in the way members of a community communicate through language and behavior, as the reflection of their minds, is an integral aspect of life to look into. One element of this is communicative competence. In order for people to succeed in their sharing anything being communicated, besides being able to produce the language in spoken or in written form accurately, they must also know which word and sentence pattern to use as well as its appropriate prosodic features. This implies that in actual communication both linguistic competence and communicative competence are equally needed and they for a successful acquisition both aspects of communication should be taught simultaneously, with theory and examples. As the acquisition of communicative competence is a long process – similar to learning language, both of these crucial competences should be taught as the child start learning the language. This method of communicative competence is usually applied in Japan – a nation that puts loosing face as a loss of existence. Therefore, as a reflective value which can be gained by Indonesia from the practice of such things in that advanced country is that children in Indonesia should also be exposed to explanations and examples of communicative competence along with linguistic competence. Key Words: communicative competence, acquisition, politeness, role and status